Advancing Paper Industry Applications with Extruded Cationic Wheat Starch as an Environmentally Friendly Biopolymer - Tara, Ahmed (Polysaccharides, 2023)
Within the domain of starch modification, the study delved into cationization of wheat starch through a laboratory-scale twin-screw extruder, exploring various processing conditions. Cationic starch, a crucial component for enhancing paper attributes like dry strength and printability, took center stage. The focus shifted towards integration into papermaking, investigating the transformative potential of reactive extrusion. By contrasting it with conventional dry-process methodology, innovative strides were unveiled. The study extended to pilot-scale extrusion, bridging the gap between laboratory experimentation and potential industrial implementation. Infused with scientific rigor, the investigation navigated the benefits brought about by reactive extrusion. Empirical insights highlighted a significant reduction in the intrinsic viscosity of extruded starch, decreasing from 170 mL·g−1 (native starch) to 100 mL·g−1 at a specific mechanical energy (SME) input of 800 kWh·t−1, demonstrating remarkable stability despite increased mechanical treatment. Moreover, beyond the critical threshold of 220 kWh·t−1, retention efficiency reached a stable plateau at 78%. The study revealed that utilizing a larger extruder slightly improved the mechanical properties of the paper, emphasizing the advantage of scaling up the production process and the consistency of results across different extruder sizes.
Keywords: cationic wheat starch; degree of substitution; packaging; papermaking; specific mechanical energy; twin-screw reactive extrusion; viscosity